The GATT, agriculture, and the developing countries - Islam, Nurul; Valdes, Alberto (International Food Policy Research Institute, 1990)
IFPRI convened a seminar on "GATT Negotiations on Agriculture and Developing Countries" on May 30-June 1, 1990, in Montreux, Switzerland, with participation by a number of distinguished experts on GATT and developing-country officials engaged in the GATT negotiations. The seminar's deliberations focused on issues of negotiation of particular interest to developing countries and options and strategies available to the developing countries that would derive significant benefits from the liberalization of world trade. The seven papers in this volume served as the context for the deliberations.